Modification of chitosan for preparation of poly(N-isopropylacrylamide/ O-nitrochitosan) interpenetrating polymer network - Rahman, N.A.; Hanifah, S.A.; Zani, A.M.N.; Ahmad, A. (Universiti Kebangsaan Malaysia, 2015)
An interpenetrating polymer network (IPN), N-isopropylacrylamide/O-nitrochitosan (NONK) was developed in the presence of ammonium persulfate using solution polymerization technique. O-nitrochitosan (ONK) was synthesized from chitosan, before it was further reacted with N-isopropylacrylamide. A new vibration of the C-N bond formed between the NH from ONK and the CH2 from NIPAAm was detected at the peak 1154 and 1171 cm-1 using attenuated total reflection Fourier-transform infrared (ATR-FTIR) spectroscopy. In the polymerization, the primary amine became a secondary amine and the peaks of the amide I (C=O peak) and amide II (N–H) were broadened. The structure of ONK was confirmed using nuclear magnetic resonance (NMR). At 10°C, the result from swelling test was found that IPN poly(NONK82) had the highest swelling percentage, 1171%, compared to poly (NIPAAm) at 467%. Micrograph from scanning electron microscopy (SEM) indicated the pore size of IPN NONK increased with an increasing ratio of ONK.